2021
DOI: 10.3389/fphar.2021.620187
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in COVID-19: Factors Associated With Mortality Before and After Treatment

Abstract: Tocilizumab (TCZ) has been administered in SARS-CoV-2 pneumonia but the factors associated with mortality before and after treatment remain unclear. Cox regression models were used to estimate the predictors of time to death in a cohort of hospitalized patients with COVID-19 receiving TCZ. In addition, the mean differences between discharged and deceased patients in laboratory parameters measured before and 3, 6 and 9 days after TCZ administration were estimated with weighted generalized estimation equations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 51 publications
(85 reference statements)
8
20
4
Order By: Relevance
“…Deceased patients had significantly lower lymphocyte counts than surviving patients, which was consistent with other cohorts that reported the same observation [32,39], one without statistical analysis [32]. Some studies reported a direct relation between blood fibrinogen level and mortality of COVID-19 patients on tocilizumab [32,39]. However, this element was not assessed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Deceased patients had significantly lower lymphocyte counts than surviving patients, which was consistent with other cohorts that reported the same observation [32,39], one without statistical analysis [32]. Some studies reported a direct relation between blood fibrinogen level and mortality of COVID-19 patients on tocilizumab [32,39]. However, this element was not assessed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to what was reported by other studies, there was an inverse relationship between platelet count and the mortality of COVID-19 patients on tocilizumab [32,39]. Deceased patients had significantly lower lymphocyte counts than surviving patients, which was consistent with other cohorts that reported the same observation [32,39], one without statistical analysis [32]. Some studies reported a direct relation between blood fibrinogen level and mortality of COVID-19 patients on tocilizumab [32,39].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations